2011
DOI: 10.1242/jcs.090951
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic association–dissociation and harboring of endogenous mRNAs in stress granules

Abstract: SummaryIn response to environmental stress, cytoplasmic mRNAs aggregate to form stress granules (SGs). SGs have mainly been studied indirectly using protein markers, but the real-time behavior of endogenous mRNAs in SGs remains uncertain. Here, we visualized endogenous cytoplasmic poly(A) + mRNAs in living mammalian cells using a linear antisense 29-O-methyl RNA probe. In arsenitestressed cells, endogenous mRNAs aggregated in granules that colocalized with SGs marked by TIA-1-GFP. Moreover, analysis of mRNA dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…More telling are FRAP studies on fluorescently labeled mRNAs, which have indicated that both rapidly exchanging and immobile fractions of a single mRNA species can exist within stress granules simultaneously. 12,128,129 Therefore, stress granules, and perhaps other granules, may indeed store a subpopulation of mRNAs, although at any moment, much of that mRNA species may switch to shuttling behavior, which could indicate a return to translation, or targeting to other mRNP granules. This is consistent with the previously proposed idea of stress granules as sites of mRNA triage, rather than just solely mRNA storage sites.…”
Section: Role Of Mrnp Granules In Mrna Stabilitymentioning
confidence: 99%
“…More telling are FRAP studies on fluorescently labeled mRNAs, which have indicated that both rapidly exchanging and immobile fractions of a single mRNA species can exist within stress granules simultaneously. 12,128,129 Therefore, stress granules, and perhaps other granules, may indeed store a subpopulation of mRNAs, although at any moment, much of that mRNA species may switch to shuttling behavior, which could indicate a return to translation, or targeting to other mRNP granules. This is consistent with the previously proposed idea of stress granules as sites of mRNA triage, rather than just solely mRNA storage sites.…”
Section: Role Of Mrnp Granules In Mrna Stabilitymentioning
confidence: 99%
“…Given the presence of translationally stalled mRNA complexes, SGs were originally hypothesized to function as storage sites for non-translating RNAs. However, fluorescence recovery after photobleaching (FRAP) analyses showed that both mRNA transcripts and nearly all protein components shuttle in and out of SGs with half-lives on the order of seconds to minutes (Kedersha et al 2005; Mollet et al 2008; Zhang et al 2011). Thus, it is difficult to envisage that SGs act as static mRNA repositories.…”
Section: Stress Granulesmentioning
confidence: 99%
“…A transgenic line expressing human WT TDP-43 or a truncation mutant, for example, exhibited severe locomotor deficits, impaired synaptic transmission, and growth defects despite an absence of detectable neuronal loss (Zhang et al, 2011). In this case, though nuclear aggregates were detected in WT-expressing worms and cytoplasmic aggregates were observed in those expressing the truncation mutant, both sets of inclusions were assessed to be relatively immobile by FRAP (Zhang et al, 2011). Importantly, RNAi of HSF1 was also found to dramatically worsen the neurological phenotype (Zhang et al, 2011).…”
Section: Als and Ftld: When Aggregation Goes Awrymentioning
confidence: 99%
“…Formation of SGs is triggered by the oligomerization of low complexity sequences contained in several RNA-binding proteins such as TIA-1 and G3BP (3,4), and SGs are generally considered as pro-survival entities, which prevent apoptosis by sequestering key signaling molecules (2). In addition, since there is a constant and rapid flux of molecules between SGs and other cytoplasmic structures, most notably the polysomes (5,6), SGs were proposed to participate in regulating the composition and functional activity of messenger ribonucleoproteins (mRNPs).…”
Section: Introductionmentioning
confidence: 99%